Variants of changes in blood pressure during its three consecutive registrations - Igor Popovych; Nataliya Kozyavkina; Liliya Barylyak; Yuliya Vovchyna; Nataliya Voronych-Semchenko; Walery Zukow; Volodymyr Tsymbryla (Kazimierz Wielki University, 2022)
Introduction and aim. Earlier we noted that the patterns of blood pressure (BP) parameters recorded three times in a row deserve special attention. The aim of this article is to classify variants of changes in systolic and diastolic BP during its three consecutive registrations. Material and methods. The object of observation were 20 volunteers: ten women and ten men aged 33-76 years with maladaptation. Systolic (Ps) and diastolic (Pd) BP was measured in a sitting position three times in a row without pause. Each patient was tested twice with a 7-day interval. Results. We confirmed the diversity of Ps2/Ps1, Ps3/Ps1, Pd2/Pd1 and Pd3/Pd1 patterns identified earlier. 5 clusters were identified. The most characteristic feature of clusters are the changes in Pd during the second registration. Instead, the contribution of changes in Ps during the second registration is minimal. It was found that in 18 members of the most numerous cluster No1, Pd is practically stable, while Ps consistently falls with each subsequent measurement. In 8 members of cluster No.4, Pd slightly but consistently decreases, and Ps slightly but consistently increases. In 4 members of cluster No.5, Pd significantly decreases at the second measurement and remains at this level at the third measurement; Ps reacts to measurements similarly, but less noticeably. In 7 members of cluster No.3, Pd significantly increases in the second measurement, but in the next one it only slightly exceeds the initial level, while Ps is practically stable. In 3 members of cluster No2, Pd increases even more during the second measurement and remains significantly higher than the initial one thereafter, while Ps steadily decreases. Conclusion. In the process of successive three-time measurement of blood pressure, changes in its values, which differ in severity and direction, were found, grouped into 5 patterns. The following article will show that each pattern is characterized by a specific constellation of parameters of the neuroendocrine-immune complex and metabolism, which determines a certain reaction to the occlusion of the brachial arteries by the factors of vasoconstriction, vasodilatation and inotropism.